Recommended Infrastructure Standards for Mass Antibiotic Dispensing - Nelson, Christopher (RAND Corporation, 2008)
A central component of public health preparedness is the ability todispense medications to large populations under short timelines. This reportpresents recommended standards for points of dispensing (or PODs), where thepublic would receive the medications. The standards, which are designed toapply to widely divergent jurisdictions, rely on expert panel evaluations,current POD planning practices, and computer-modeled scenarios.